Qur’anic Pedagogy for Interreligious Tolerance in Islamic Religious Education - Supriadi, Udin; Rahmat, Munawar; Subakti, Ganjar Eka; Firmansyah, Mokh. Iman; Sumarna, Elan; Nurjanah, Nunuy (Jurnal Pendidikan Islam, 2025)
Religious prejudice among students poses a serious challenge to Islamic education in pluralistic societies. This study aims to examine the effectiveness of the Qur’an-based Religious Diversity (QbRD) method in reducing religious prejudice among Muslim university students. Employing a mixed-methods design, the research combined the qualitative development of Islamic Religious Education (IRE) materials with a quasi-experimental quantitative approach. The QbRD learning model was implemented in four stages: (1) student-led discussions on the concepts of faith and disbelief; (2) lecturer-led reflection on the Islamic mission of moral excellence; (3) student analysis of Qur’anic verses concerning Muslims and non-Muslims; and (4) student synthesis of theological perspectives based on the Qur’an. The study involved 12 IRE classes, with 200 students in the intervention group and 200 in the non-intervention group. Statistical analysis showed a significant improvement in the intervention group’s positive religious attitudes (t = 16.925, p < 0.01), while the control group showed minimal change. These findings indicate that QbRD fosters inclusive theological understanding and interfaith tolerance among students. The study suggests that Qur’an-based and dialogical pedagogies can play a transformative role in Islamic education, particularly in universities and pesantren, to promote peace and religious moderation.